2009
DOI: 10.1136/emj.2006.035725
|View full text |Cite
|
Sign up to set email alerts
|

Tension pneumothorax secondary to automatic mechanical compression decompression device

Abstract: The details are presented of the first published case of a tension pneumothorax induced by an automatic compression-decompression (ACD) device during cardiac arrest. An elderly patient collapsed with back pain and, on arrival of the crew, was in pulseless electrical activity (PEA) arrest. He was promptly intubated and correct placement of the endotracheal tube was confirmed by noting equal air entry bilaterally and the ACD device applied. On the way to the hospital he was noted to have absent breath sounds on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…We presume that these pneumothoraces were caused by injury of the pleura secondary to rib or sternal fractures. In some cases, tension pneumothorax may occur 9,22 . With regard to haemopericardium, there were 14 cases (6.3%) in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We presume that these pneumothoraces were caused by injury of the pleura secondary to rib or sternal fractures. In some cases, tension pneumothorax may occur 9,22 . With regard to haemopericardium, there were 14 cases (6.3%) in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…12 Second, there is an emerging need for a systematic study of injuries associated with the novel mechanical compression devices that are becoming increasingly popular. 12 Case reports illustrating catastrophic injuries associated with their use have appeared in recent years, [13][14][15][16] but similar injuries have also been described in the context of manual compression 1,[17][18][19][20] and systematic studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…For an overview of more mechanical devices from different manufacturers, please refer to recent review articles in this area [33,36]. Earlier studies have reported a higher incidence of rib and sternal fractures after manual ACD versus conventional manual CPR [37]; other case reports have described rare complications, such as tension pneumothorax [38] and liver [39] or splenic lacerations [40]. Nevertheless, neither of these are thought unique to automated versus conventional manual chest compressions [41].…”
Section: Automated Chest Compressionmentioning
confidence: 99%